Competitiveness of Chinese Firms West Meets East - Li-Hua, R. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This book addresses the multi-facet competitiveness of firms in China from an angle of strategic management of technology and innovation. The Chinese vanguard companies have been excellent in identifying strategic position and appropriately making strategic decisions, and effectively making strategy in action.